Pengukuran Destination Awareness Wisatawan Domestik pada Candi Muaro Jambi - Hetty Karunia Tunjungsari; Frangky Selamat; Chairy Chairy (Jurnal Komunikasi, 2019)
This research focuses on measuring the destination awareness of domestic tourists in a number of tourist destinations in Indonesia. Questionnaire-based survey was conducted by researchers to find out how domestic tourists' destination awareness of tourist destinations: Borobudur, Monas, Ulundanu Temple, Tana Toraja, and Muaro Jambi Temple. The main purpose of this destination awareness measurement is to confirm presupposition that in general there are still very limited domestic tourists who are aware of Muaro Jambi Temple as one of tourist’s destination in Indonesia. Research hypothesis is proposed with the allegation that there are differences in the destination awareness of domestic tourists towards the tourist destinations of Borobudur, Monas, Ulundanu Temple, Tana Toraja, and Muaro Jambi Temples. Muaro Jambi Temple is suspected to have the lowest level of awareness compared to other tourist destinations. The hypothesis in this study is supported by data, the level of awareness of domestic tourists over Muaro Jambi Temple is lower than the level of awareness of the Borobudur, Monas, Ulundanu Temples, and Tana Toraja. Theoretically the results of this study bring scientific contributions related to the field of destination marketing, specifically related to the destination awareness of a domestic tourist destination. Practically, the results of this study can become the basis for establishing destination marketing policies aimed at increasing domestic tourist awareness of various tourist destination in Indonesia. Penelitian ini berfokus pada pengukuran destination awareness wisatawan domestik sejumlah destinasi wisata di Indonesia. Survei berbasis kuesioner dilakukan oleh peneliti untuk mengetahui bagaimana destination awareness wisatawan domestik terhadap destinasi wisata Candi Borobudur, Monas, Pura Ulundanu, Tana Toraja, dan Candi Muaro Jambi. Tujuan utama pengukuran destination awareness ini adalah untuk mendapatkan dukungan terhadap dugaan peneliti bahwa secara umum wisatawan domestik yang mengenal Candi Muaro Jambi sebagai pilihan destinasi wisata di Indonesia masih sangat terbatas. Hipotesis dalam penelitian ini diajukan dengan dugaan bahwa terdapat perbedaan destination awareness wisatawan domestik terhadap destinasi wisata Candi Borobudur, Monas, Pura Ulundanu, Tana Toraja, dan Candi Muaro Jambi. Candi Muaro Jambi diduga memiliki tingkat awareness yang paling rendah dibandingkan dengan destinasi wisata lain yang diteliti. Hipotesis dalam penelitian ini didukung oleh data, tingkat awareness wisatawan domestik atas Candi Muaro Jambi lebih rendah dibandingkan dengan tingkat awareness atas Candi Borobudur, Monas, Pura Ulundanu, dan Tana Toraja. Secara teoretis, hasil penelitian ini memberikan kontribusi ilmiah terkait dengan bidang pemasaran destinasi, khususnya terkait dengan destination awareness suatu destinasi wisata domestik. Secara praktis, hasil penelitian ini dapat menjadi dasar pembentukan kebijakan pemasaran destinasi yang bertujuan untuk meningkatkan awareness wisatawan domestik terhadap berbagai destinasi wisata yang ada di Indonesia.